Anticholinergic Burden Rationalisation Before Dementia Treatment in an Old Age Psychiatry Community Team - Isaac Alakeji; Aruna Ravishankar; Siobhan Jeffery (BJPsych Open)
Aims: To carry out a retrospective audit of medical records of people with newly diagnosed dementia in North Devon Community Older People’s Mental Health Team for any evidence of anticholinergic burden review before dementia treatment.